Flexible non-metallic electro-conductive textiles. Issue 1 (2nd January 2017) - Maiti, Syamal; Das, Dipayan; Sen, Kushal
ABSTRACT: This issue of Textile Progress reviews research carried out on electrically conducting polymers, fibres and fabrics prepared by in situ chemical, electrochemical and vapour-phase polymerisation. It provides information about various inherently conducting polymers prepared from aniline, pyrrole, thiophene and their derivatives that are often used to prepare flexible non-metallic electro-conductive textiles. Several methods for the characterisation of electro-conductive fabrics are included, namely scanning electron microscopy, X-ray diffraction, elemental disruptive X-ray analysis and Fourier transmission infrared spectroscopy. The role of the polymerisation process in determining the electrical properties of electro-conductive textiles is examined. The review highlights applications of flexible non-metallic conductive textiles in electro-magnetic shielding materials, heating pads, sensors and actuators.